Towards adopting software quality assurance in agile development methodology - Shuib, Rosnani; Hassan, Sa'adah (Science Research Society, 2021)
In agile software development methodology, software product is developed through a few iterations and delivered incrementally. In spite of the known benefits of the agile methodology, yet issue still exists in developing high-quality software product using this methodology. Hence, quality assurance mechanism should be in place in agile development to ensure quality adherence to the software product. However, taking up quality assurance in agile software development is not an easy task as it has its own manifesto and principles that need to be met. Thus, this paper highlights the issues and challenges towards adopting quality assurance in agile development methodology. Particularly, in aniteration where we need to assure that the product increment meets the requirements as well as to decide the requirements for next increment and iteration planning. Subsequently, few measuresare identifiedconcerning the issues. The discussion in this paper is based on Scrum case, yet still relevant to other types of agile methodologies.